Shortened of the crown and root lengths of the mandibular permanent molar in beta major thalassemia children - Primathena, Indra; Riyanti, Eriska; Firman, Ria Noerianingsih (Padjadjaran Journal of Dentistry, 2011)
Beta major thalassemia is a genetically inherited blood disorder due to a genetic mutation on the polypeptide chains of hemoglobin which is manifested in the growth and development of the tooth. The objectives of the investigation were to obtain differences of the crown and root lengths of the mandibular first right side permanent molar between beta major thalassemia children and normal children group at the matching ages of 11 to 13 years old. The descriptive comparative method was used in the study and samples were selected using the purposive sampling technique. Sample numbers, which were obtained using the consecutive sampling technique, consists of 12 children of beta major thalassemia and 12 of normal children at the matching ages of 11 to 13 years. Periapical radiographs of both thalassemia and normal children were administered using the method of Seow and Lai. Data were analyzed using t-test method. The study revealed that the crown and root lengths of the mandibular first right side permanent molar of beta major thalassemia children were shorter than normal children at the ages of 11 to 13 years.